Spontaneous planning units in the structure of a large city - Kukina, Irina; Fedchenko, Irina (project baikal, 2025)
Modern urban development conditions do not allow achieving the integrity of urban space. The formation of spontaneous planning units in the structure of a large city is due to the liberalization of regulations for architectural and urban development activities, a departure from large-scale projects and ensemble concepts. The study of the morphology of the city allows us to propose their approximate typology: urban growth cores; transit-oriented areas; natural areas; heterogeneous residential areas; ‘in-between territories’; terrain vague, etc. The nature of each type suggests a targeted research methodology and development strategies.
Keywords: spontaneous planning units; morphology; typology; research methodology